Integrating Socio-Cultural Factors into Pig Agribusiness Value Chains: Insights from a Systematic Review in Papua - Marthina Milka Bless; Sangle Y. Randa; Mulyadi Djaya (Journal of Mandalika Social Science, 2026)
Pig farming plays a strategic role in both the agribusiness system and the socio-cultural life of Papuan communities. However, the development of pig farming enterprises still faces various challenges, particularly in terms of production, economic performance, and environmental management. This study aims to analyze the pig agribusiness system in Papua using a systematic literature review approach, with a particular focus on integrating socio-cultural factors into a value chain framework. The method follows the PRISMA guidelines, including identification, screening, eligibility, and inclusion stages, resulting in the selection of 30 relevant scientific articles.  The findings indicate that pig farming systems in Papua are predominantly traditional, characterized by relatively low productivity, influenced by factors such as feed, labor, farming experience, and litter size. At the same time, pigs hold significant socio-cultural value, functioning as symbols of social status, instruments of customary exchange, and means of strengthening social relationships. Importantly, the study reveals that socio-cultural factors are not merely external influences but are embedded within each stage of the value chain, shaping production practices, distribution mechanisms, and consumption patterns. Economically, pig farming contributes to household income, yet it remains technically and economically inefficient. Environmental issues, particularly related to waste management, also represent a major challenge. Furthermore, the agribusiness value chain of pig farming has not been optimally integrated, especially in terms of processing, distribution, and institutional support. This study identifies a research gap in the limited integration of socio-cultural dimensions within value chain-based agribusiness development. Therefore, a holistic and context-specific development approach is required to enhance the sustainability of pig agribusiness in Papua.